Preparation of Film Containing Polyelectrolyte Complex for Topical Delivery of Penciclovir - Mina Emaad Taha; Maraie, Nidhal Khazaal (Iraqi Journal of Pharmaceutical Sciences, 2025)
Abstract A thin film refers to a pliable polymer layer, with or without a plasticizer, that has been observed to enhance the onset of medicine action, reduce dosing frequency, and enhance the efficacy of drugs. One such technique involves the utilization of polyelectrolyte complexes (PEC) in the preparation of films. This work concerned with studying variables affecting the preparation of topical film for penciclovir using PEC of chitosan and acacia. In this study, Skin bioadhesive polymeric films were fabricated using a solvent casting approach, using acacia gum and chitosan as the main components. The resulting films were further examined to evaluate their features and drug release qualities. PEC films were prepared with different molar ratio and concentration of acacia and chitosan, different PH, and type of chitosan. The produced films undergo evaluation in terms of their percent encapsulation efficiency (%EE), film thickness, folding endurance, swelling index, and drug release. The best film had 90 % entrapment efficiency, suitable swelling index, good bioadhesion force, and showed 50% drug release after 6 hours, which reach 100 % after 12 hours. The Fourier Transform Infrared investigation demonstrated the formation of PEC. The prepared bioadhesion film could be considered suitable for topical application to improve patient compliance compared to the available topical cream.